CD74-Downregulation of Placental Macrophage-Trophoblastic Interactions in Preeclampsia. Issue 1 (24th June 2016) - Przybyl, Lukasz; Haase, Nadine; Golic, Michaela; Rugor, Julianna; Solano, Maria Emilia; Arck, Petra Clara; Gauster, Martin; Huppertz, Berthold; Emontzpohl, Christoph; Stoppe, Christian; Bernhagen, Jürgen; Leng, Lin; et al.
Abstract : Rationale: : We hypothesized that cluster of differentiation 74 (CD74) downregulation on placental macrophages, leading to altered macrophage-trophoblast interaction, is involved in preeclampsia. Objective: : Preeclamptic pregnancies feature hypertension, proteinuria, and placental anomalies. Feto-placental macrophages regulate villous trophoblast differentiation during placental development. Disturbance of this well-balanced regulation can lead to pathological pregnancies. Methods and Results: : We performed whole-genome expression analysis of placental tissue. CD74 was one of the most downregulated genes in placentas from preeclamptic women. By reverse transcriptase-polymerase chain reaction, we confirmed this finding in early-onset (<34 gestational week, n=26) and late-onset (≥34 gestational week, n=24) samples from preeclamptic women, compared with healthy pregnant controls (n=28). CD74 protein levels were analyzed by Western blot and flow cytometry. We identified placental macrophages to express CD74 by immunofluorescence, flow cytometry, and RT-PCR. CD74-positive macrophages were significantly reduced in preeclamptic placentas compared with controls. CD74-silenced macrophages showed that the adhesion molecules ALCAM, ICAM4, and Syndecan-2, as well as macrophage adhesion to trophoblasts were diminished. Naive and activated macrophages lacking CD74 showed a shift toward a proinflammatory signature with an increased secretion of tumor necrosis factor-α, chemokine (C–C motif) ligand 5, and monocyte chemotactic protein-1, when cocultured with trophoblasts compared with control macrophages. Trophoblasts stimulated by these factors express more CYP2J2, sFlt1, TNFα, and IL-8 . CD74-knockout mice showed disturbed placental morphology, reduced junctional zone, smaller placentas, and impaired spiral artery remodeling with fetal growth restriction. Conclusions: : CD74 downregulation in placental macrophages is present in preeclampsia. CD74 downregulation leads to altered macrophage activation toward a proinflammatory signature and a disturbed crosstalk with trophoblasts. Abstract : Supplemental Digital Content is available in the text.